DETEKSI JATUH PADA LANSIA DENGAN MENGGUNAKAN AKSELEROMETER PADA SMARTPHONE - Mardi Hardjianto; M. Ainur Rony; Guntur Sarwo Trengginas (SENTIA 2016, 2016)
Fall can cause injury effects, such as sprains, fractures and concussions. It can even lead to someone's death. Elderly people who have fallen can cause psychological disorders such as loss of self esteem and feelings of fear that they will fall again. As the effects of the fall, the elderly become afraid of walking in order to avoid the danger of falling. Therefore, an application to detect whether the events fall or not is needed. The aim of this study is to identify the occurrence of falls using a threshold-based methods. The sensors used to detect fall are the accelerometers located on Android smartphone devices. If the data from the sensor exceeds a predetermined threshold value, then it is identified as fal and the app will send a short message to supervisors and family members so that the elderly can be helped immediately.